Pulmonary prophylactic impact of melatonin and/or quercetin: A novel therapy for inflammatory hypoxic stress in rats - Al-Rasheed Nouf M.; Fadda Laila; Attia Hala A.; Sharaf Iman A.; Mohamed Azza M.; Al-Rasheed Nawal M. (Acta Pharmaceutica, 2017)
The study aims to compare, through histological and biochemical studies, the effects of quercetin, melatonin and their combination in regulation of immuno-inflammatory mediators and heat shock protein expressions in sodium nitrite induced hypoxia in rat lungs. The results revealed that NaNO2 injection caused a significant decrease in Hb in rats, while serum levels of TNF-α, IL-6 and CRP, VEGF and HSP70 were elevated compared to the control group. Administration of melatonin, quercetin or their combination before NaNO2 injection markedly reduced these parameters. Histopathological examination of the lung tissue supported these biochemical findings. The study suggests that melatonin and/or quercetin are responsible for lung tissue protection in hypoxia by downregulation of immuno-inflammatory mediators and heat shock protein expressions. Pre-treatment of hypoxic animals with a combination of melatonin and quercetin was effective in modulating most of the studied parameters to near-normal levels.